Problematizando as diferentes formas de provimento da gestão escolar nos municípios sul-rio-grandenses - Silveira, Carmem Lucia Albrecht da (2015)
The dissertation studies the management of public schools linked to municipal educational system of Rio Grande do Sul . The problem of research focuses on the different ways of filling the post of director / school manager in order to identify aspects that can support the debate on the democratic management of public education. Methodologically, the research was structured from a documentary research (laws and sites of municipal governments and the Court of Justice of Rio Grande do Sul ) and a field research. From the 497 cities of Rio Grande do Sul was possible to collect information from 158 cities for the different forms of provision: a) direct election; b) indication from the local executive; c) public tender; d) mixed form (combination of two or more types). The unveiling of the nuances of school management was given by the packaging results in accordance with the organization established by the Brazilian Institute of Geography and Statistics - IBGE in Meso and Micro-regions, and the size of each city, facilitating the intersection of indicators highlighted. The study may help other discussions about the different forms of provision adopted by several cities of Rio Grande do Sul (with different sizes and geographic locations); since the noticeable effects of these forms of provision (the subject legalization) provide findings for the related debate to democratization of school management. It is considered essential to persevere and preserve democracy as signaling democratic management in education and that, on the edges and crevices, meet forms that this model will last for the future.